The Influence of Digital Finance on the Innovation Capability of Cities in Western China - Yinyan Shu (Forest Chemicals Review, 1970)
In this paper, the panel data of 87 cities in western China from 2011 to 2016 were used to empirically analyze the influence of digital finance on the innovation capability of cities in western China. The results show that the development of digital finance has a significant positive impact on the innovation capability of western cities. China should fully tap the development potential of digital finance in western China, improve the ecological environment of digital finance development in western China, strengthen the financial knowledge education of digital financial users, encourage digital financial institutions to adhere to the inclusive orientation to promote the sinking of services, encourage digital financial institutions to optimize the product and service structure, speed up the transformation and upgrading, and play a more effective supporting role in enhancing the innovation capability of cities in western China.